SOBRE EL LLENGUATGE CINEMATOGRÀFIC DE WERNER SCHROETER A MALINA, A PARTIR DE LA NOVEL·LA D’INGEBORG BACHMANN, AMB GUIÓ D’ELFRIEDE JELINEK - M. Loreto Vilar (Anuari de Filologia: Literatures Contemporànies, 2015)
This paper provides an approach to the cinematic language in the film Malina (1991), directed by Werner Schroeter after Ingeborg Bachmann’s homonymous novel, script by Elfriede Jelinek. Working on the study by Ute Seiderer (1994) and the information provided by film editor Juliane Lorenz, the exposition and analysis of the mise-en-scène focuses on the following items: the temporal sequencing, the insinuatio in the film, the interaction between physical and psychological space, the music and the visual narrative of the end of the woman. Explored are also the motifs of ubiquitous fire, the crack in the wall and the game of mirrors. Together with the representation of the Malina character, they materialize the duality in the psyche of the woman writer in the main role and her struggle for existence.